KORELASI MODEL PEMBELAJARAN BERBASIS MASALAH (PROBEM BASED LEARNING) DENGAN PEMAHAMAN PAI SISWA DI SMP SUNAN AMPEL SUMBEREJO BANYUPUTIH SITUBONDO TAHUN 2020-/2021 - Kandiri Kandiri; Hairul Puadi (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2021)
If we are more concerned deeply to Curriculum 13 in all of Indonesia's educational stage, so we can find it has learning focused on scientific approach including observing, asking, trying, associating, communicating. It is relevant with interest student to get much knowledge with main characteristic like a) using real-world problems, b) focused learning on problem-solving, c) learning objectives are determined by students, d) teacher as a facilitator, who also has skills to solve problems. this research uses Quantitative approach to collecting data, including observation, documentation, questionnaires. the subject of research is students of SMP Sunan Ampel. Research orientation aimed in order to know the correlation of problem-based learning models with students' understanding of Islamic education at SMP Sunan Ampel Sumberejo Banyuputih Situbondo. With the research results: there is a correlation "moderate" Problem Based Learning Model with students' understanding of Islamic Education at SMP Sunan Ampel Sumberejo Banyuputih Situbondo.